Persuasive Communication in Digital Philanthropy: Bridging the Zakat Intention-Behavior Gap on Instagram - Agustin Santriana Wijayant; Asep Suryana; Hadi Suprapto Arifin (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This research investigates how Islamic philanthropic institutions employ digital persuasive communication strategies on Instagram to bridge the critical intention-behavior gap following public trust deficits. By integrating persuasive message design with an extended Theory of Planned Behavior (TPB), this study examines the impact of institutional trust-building, visual social proof (social norms), and instructional clarity (perceived ease of transaction) in predicting digital zakat behavior. An explanatory quantitative survey was conducted among 385 active Instagram followers of Rumah Zakat Indonesia, with data analyzed using the PLS-SEM algorithm. The findings reveal that visual social proof, manifested as a digital bandwagon effect, is the most dominant persuasive predictor of the audience's zakat intention. Crucially, trust-building messages lack a significant direct effect on actual behavior, requiring the audience's intention as a full mediator. Furthermore, clear instructional communication regarding digital transaction functions as a 'moral nudge' that directly facilitates spontaneous giving. To optimize digital philanthropy, persuasive communication campaigns must move beyond generic transparency claims and prioritize influencer-driven social proof combined with frictionless digital call-to-actions.